VALIDITY OF LEARNING MEDIA BASED ON DIAMOND TOUCH CARDBOARD WITH THINK PAIR SHARE MODEL AND STUDENT RESPONS ON EXCRETORY SYSTEM MATERIAL - Khumaeroh, Mega Siti; Ratnasari, Jujun; Ramdhan, Billyardi (Journal of Biology Education, 2019)
This study aims to reseach and develop the use of Diamond Touch media with think Pair share models. The research held at Pondok Modern Assalam Putri, Sukabumi with 31 student. The feasibility of the media used and evaluated by media expert and small-scale trials, Diamond touch is a medium that can be used as a medium to achieve goals material in learning Biology, formal and non-formal education. The elements contained in Diamond Touch media are (1) learning messages or core material (2) cardboard tools for learning aids. The results of this study that Diamond touch media can be integrated with learning models namely Think Pair Share so that the learning process is not boring and Diamond touch media is very valid for use in learning. Analysis of validity test data obtained through questionnaires was performed using quantitative data processing formulas